The goals and the value business angels perceive from their investment activity - Escorrega, Rui Manuel Falcão Guerreiro (2023)
Business angels (BAs), also designated as angels, play a vital role in the process of emergence and nurturing entrepreneurial startups at their early stages and keep growing in number and relevance. However, today, they face dramatic challenges from the increasing organisation of their activity through professionalised angel groups. New players (e.g. crowdfunding, venture capital) are also entering their natural arena of early-stage investments. Therefore, this is a critical moment, in which the scientific community and the BAs may reflect and create knowledge about the new way of acting and investing of these investors. The overall purpose of this doctoral thesis is to develop a deeper understanding of the goals and the value angels currently perceive from their investing activity. First, angel goals were analysed under an approach proposing consumer behaviour and perceived value as a new lens of an integrative analysis with the conventional economic and financial views, to obtain a more holistic, richer, and precise view of the angel behaviour. Second, the perceived investment value, already applied to stock market investors, was extended to the angel scope to measure the type of values angels perceive from their activity and their impact on job satisfaction and reinvestment. Third, the angel activity was analysed through the career development theory perspective to uncover the internal motives that drive individuals to invest their money and effort following an angel career. Fourth, since calling became, in recent years, a fundamental topic in work and career development, part of the research was conducted to measure the impact of calling on the angels’ involvement in their activity, and on the value they perceive from it. Both qualitative and quantitative methodologies are adopted: the former is based on interviews with BAs and on the laddering technique; and the latter on structural equation modelling techniques, with which responses of angels worldwide to questionnaires were analysed. This thesis highlights that becoming a BA enhances the opportunity for achieving a high diversity of interrelated goals such as self-development, co-creating value with the entrepreneurs, earning money, having fun and experiencing emotional excitement from investing in startups. The importance of addressing angel activity as a career development process is reinforced. The perception of getting value with the investing activity, including career development, also makes BAs more satisfied and more likely to reinvest. Moreover, those BAs who see their work as a calling are more likely to perceive value from angel investing and more likely to be involved in angel activity. For many individuals, being a BA is not exclusively a financial game; the journey of being an angel is more important than the financial outcome. The “journey” is itself the destination. Finally, crucial implications were identified for angel groups, entrepreneurs and the entire BAs’ ecosystem. The angel experience is personal and non-delegable. Therefore, angels should not be prevented from reaching their deepest personal goals aligned with their lives. Professionalised groups and entrepreneurs should create conditions to let the angels live the angel experience they intend to live, being encouraged to achieve their most important goals. If this happens, BAs will feel more satisfied, increasing their reinvestment opportunities and remaining for a long term in the BAs’ career.